Effects of short-term fine particulate matter exposure on acute respiratory infection in children - Kim, Kyoung Nam; Kim, Soontae; Lim, Youn Hee; Song, In Gyu; Hong, Yun Chul (International Journal of Hygiene and Environmental Health, 2020)
Background: Previous studies on the association between fine particulate matter (PM2.5) exposure and acute respiratory infection in children are scarce and present inconsistent results. We estimated the association between short-term PM2.5 exposure and acute respiratory infection among children aged 0–4 years using a difference-in-differences approach. Methods: We used data on the daily PM2.5 concentrations, hospital admissions for acute respiratory infection, and meteorological factors of the 15 regions in the Republic of Korea (2013–2015). To estimate the cumulative effects, we used a difference-in-differences approach generalized to multiple spatial units (regions) and time periods (day) with distributed lag non-linear models. Results: With PM2.5 levels of 20.0 μg/m3 as a reference, PM2.5 levels of 30.0 μg/m3 were positively associated with the risk of acute upper respiratory infection (relative risk (RR) = 1.048, 95% confidence interval (CI): 1.028, 1.069) and bronchitis or bronchiolitis (RR = 1.060, 95% CI: 1.038, 1.082) but not with the risk of acute lower respiratory infection and pneumonia. PM2.5 levels of 40.0 μg/m3 were also positively associated with the risk of acute upper respiratory infection (RR = 1.083, 95% CI: 1.046, 1.122) and bronchitis or bronchiolitis (RR = 1.094, 95% CI: 1.054, 1.136). Conclusions: We found the associations of short-term PM2.5 exposure with acute upper respiratory infection and bronchitis or bronchiolitis among children aged 0–4 years. As causal inference methods can provide more convincing evidence of the effects of PM2.5 levels on respiratory infections, public health policies and guidelines regarding PM2.5 need to be strengthened accordingly.
Keywords: Acute Disease; Air Pollutants; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Inhalation Exposure; Male; Particulate Matter; Republic of Korea; Respiratory Tract Infections; Bronchiolitis; Bronchitis; Causal inference method; Difference-in-differences; Fine particulate matter; Upper respiratory infection